1997
DOI: 10.1101/lm.4.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Association of visual objects and olfactory cues in Drosophila.

Abstract: IntroductionContext-dependent preferences in a choice between an upper and a lower visual object of otherwise identical appearance were recorded during stationary flight of the fruitfly, Drosophila melanogaster, in a flight

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Homogeneous backgrounds of vertical stripes During tethered flight, Drosophila can learn to recognize specific elements of a random checkerboard pattern (Dill et al, 1993). Pattern recognition enables them to 'recall' the spatial orientation of a visual pattern associated with an olfactory stimulus (Guo and Götz, 1997). These findings support the hypothesis that flies match spatially unique elements of the visual world with the strength of olfactory stimuli and might explain why flies in our experiments required a textured visual surround to localize an odor.…”
Section: Uniform White and Random Checkerboard Backgroundssupporting
confidence: 77%
“…Homogeneous backgrounds of vertical stripes During tethered flight, Drosophila can learn to recognize specific elements of a random checkerboard pattern (Dill et al, 1993). Pattern recognition enables them to 'recall' the spatial orientation of a visual pattern associated with an olfactory stimulus (Guo and Götz, 1997). These findings support the hypothesis that flies match spatially unique elements of the visual world with the strength of olfactory stimuli and might explain why flies in our experiments required a textured visual surround to localize an odor.…”
Section: Uniform White and Random Checkerboard Backgroundssupporting
confidence: 77%
“…Our results in this study, together with previous studies, demonstrate that a wide variety of odor stimuli can elicit flight maneuvers (Budick and Dickinson, 2006;Chow and Frye, 2008;Duistermars et al, 2009a;Duistermars et al, 2009b;Duistermars and Frye, 2008;Frye and Dickinson, 2004;Guo and Gotz, 1997;Wolf and Heisenberg, 1991;Xi et al, 2008). However, in all these cases the odor stimuli were presented at relatively high concentrations, ranging from pure odor to 100-fold diluted.…”
Section: Olfactory Input To a Single Glomerulus Can Trigger Both Turnmentioning
confidence: 68%
“…Several studies have shown that odor stimuli cause tethered Drosophila to increase their wingbeat frequency and amplitude, and/or to modulate their flight direction (Chow and Frye, 2008;Duistermars et al, 2009a;Duistermars et al, 2009b;Duistermars and Frye, 2008;Frye and Dickinson, 2004;Guo and Gotz, 1997;Wolf and Heisenberg, 1991;Xi et al, 2008). In this study, our broad aim was to investigate the relationship between these flight behaviors and primary sensory neuron activity.…”
Section: Introductionmentioning
confidence: 99%
“…The flight control system is therefore compacted into relatively few neurons, making flies particularly useful for studying the neurobiology of complex behavior (Frye and Dickinson, 2001). Drosophila melanogaster, in particular, has emerged as a key model system to investigate moleculargenetic, developmental and physiological determinants of olfactory discrimination (Stensmyr et al, 2003;Vosshall, 2000), visual motion detection (Barth et al, 1997;Gibbs et al, 2001;Juusola and Hardie, 2001;Wolf and Heisenberg, 1990), as well as associative learning and memory formation (Connolly et al, 1996;deBelle and Heisenberg, 1994;Guo and Götz, 1997;Pascual and Preat, 2001). Recent advances in targeted genetic manipulations such as the pGAL4 enhancer-trap system (Brand and Perrimon, 1993) have catalyzed the identification of anatomical sites of multimodal integration (Ito et al, 1998), functional roles of central brain structures, and sensorimotor synapses and peripheral sensory pathways involved in gross locomotor performance (Kitamoto, 2001;Strauss, 2002).…”
Section: Free-flight Odor-search Behavior In Drosophilamentioning
confidence: 99%